Michael Addition Initiated Substrate- or Catalyst-Controlled Chemodivergent Three-Component Construction of Fused and Bridged Polycyclic Heterocycles - Du, Haiying; Rodriguez, Jean; Bugaut, Xavier; Constantieux, Thierry (Synthesis, 2015)
The results on the multicomponent reaction between cyclic β-keto esters, enals, and simple primary aliphatic amines are reported. In thermal conditions in the presence of 4 Å molecular sieves, two different families of heterocyclic products (aminobicyclo[3.3.1]nonanones or cycloalka[b]piperidines) were obtained depending on the presence of a substituent in the α-position of the aldehyde. Moreover, preliminary results on the possibility to obtain these two bicyclic cores from the very same starting materials by introducing organocatalysts with different activation modes in the reaction are presented.
Keywords: 1,3-dicarbonyls; heterocycles; Michael addition; multicomponent reaction; organocatalysis